Evaluation of business process in convention production companies using business process improvement (BPI) - Syarifudin, Nur Afan; Izzuddin, Muhammad Daffa; Amaliyah, Tazkiyatun Aeni (Journal of Soft Computing Exploration, 2022)
This research aims to choose the best business process model for a convection company during the COVID-19 pandemic. This study applies an analytical framework of business process improvement (BPI), including five whys analysis (organizing for improvement, understanding the process, streamlining, measurement and controls, continuous improvement). Model business process modeling and notation (BPMN). The results of this study are an analysis of business processes that occur in convection companies, and the results are that the business processes in convection companies are still less effective. In addition, the author also provides recommendations, namely the use of a database on the ordering system used evaluation of business processes in convection production companies using BPI and BPMN.